Preliminary Phytochemical Screening, LC-MS, FT-IR and HPTLC Analyses, and Evaluation of Antioxidant and Antimicrobial Activities of Ethanolic Extracts of Crataeva nurvala Bark - Chaddha, Varun; Gupta, Reena (Anti-Infective Agents, 2026)
IntroductionThe bioactive constituents found in herbal medicines play a crucial role in their therapeutic effects. Crataeva nurvala is a well-known medicinal plant, traditionally used for the treatment of kidney and bladder-related ailments. In Ayurveda, its bark has been employed for over 3,000 years as a natural remedy for various kidney disorders.ObjectiveIn this research article, the ethanolic bark extract of Crataeva nurvala was characterized through physical evaluation, preliminary phytochemical screening, LC-MS, FT-IR, and HPTLC analyses, along with assessments of its antioxidant and antimicrobial activities.MethodsThe extraction process was performed using petroleum ether, and 150 g of weighed Crataeva nurvala powdered bark was carried out in a Soxhlet apparatus for 36 hours. The extraction was completed by putting one drop from a thimble onto a filter paper that exhibited no oil spots. The bark marcs were removed and allowed to dry before being individually exposed to a 24-hour hot extraction process using 90% ethanol in a soxhlet apparatus. The solvent was vaporized and concentrated to produce a dry residue after the extraction.Results and DiscussionLC-MS analysis identified several major phytoconstituents in the ethanolic extract, including scoulerin, formononetin, L-carnosine, resveratrol, flavanone, quercetin, kaempferide, rhamnetin, daidzein, and isorhamnetin. FT-IR spectroscopy revealed characteristic peaks corresponding to various functional groups present in the extract. HPTLC studies confirmed the presence of active compounds, such as lupeol and gallic acid. Phytochemical screening of Crataeva nurvala bark extract further detected saponins, glycosides, alkaloids, anthraquinones, flavonoids, and tannins. This study also demonstrated notable antioxidant and antimicrobial activities associated with the plant extract.ConclusionIt can be concluded that Crataeva nurvala bark contains numerous bioactive compounds, making it a valuable plant for phytopharmaceutical applications. The ethanolic extracts of Crataeva nurvala bark demonstrated significant antioxidant and antimicrobial activities. For the first time, LC-MS and HPTLC analyses revealed high contents of L-anserine nitrate, resveratrol, flavanone, chlorogenic acid hemihydrate, quercetin, kaempferide, isorhamnetin, rhamnetin, gallic acid, and lupeol, which likely contribute to these biological effects. Additionally, the study suggests that the ethanolic extract may possess antibiotic, anti-inflammatory, antibacterial, antioxidant, antidiabetic, anticancer, and anti-obesity properties due to the presence of 16 phytochemical compounds identified by LC-MS. Fluorescent analysis of the bark powder showed characteristic coloration upon exposure to various chemical reagents, supporting the presence of diverse phytochemicals. Preliminary phytochemical screening further confirmed the presence of saponins, alkaloids, flavonoids, anthraquinones, glycosides, and tannins in the ethanolic bark extract.
Keywords: LC-MS analysis